Responses of vegetation low-growth to extreme climate events on the Mongolian Plateau - Hao Li; Yunfeng Hu; Batunacun (Global Ecology and Conservation)
Since the 21st century began, the frequency and intensity of extreme climate events have significantly increased globally, becoming a widely recognized phenomenon of global change. These extreme events, including droughts and heatwaves, have profound impacts on the structure and function of ecosystems. This study focuses on the Mongolian Plateau. It utilizes meteorological and remote sensing vegetation data, combined with consistency and sensitivity analyses. These approaches aim to provide an in-depth understanding of the relationship between various extreme climate events and vegetation low-growth. The study found that extreme drought and extreme heat events are the primary drivers affecting vegetation low-growth on the Mongolian Plateau. The analysis results indicate that the sensitivity of vegetation to these extreme climate events is regulated by regional hydrothermal conditions, with vegetation in long-term drought areas being more susceptible to the suppression of extreme drought, while humid areas exhibit some resistance. As the temperature gradient increases, the sensitivity of vegetation to extreme high temperatures increases, while sensitivity to extreme low temperatures decreases. Furthermore, the study also revealed differences in the responses of different vegetation types to extreme events under the same climatic conditions, highlighting the ecological basis of ecosystem resilience and adaptability. This research not only enhances our understanding of vegetation dynamics under the influence of extreme climate events but also provides scientific evidence for ecological management and climate adaptation in the Mongolian Plateau region.